EFEKTIVITAS MODEL PENDEKATAN PEMBELAJARAN BAHASA AKADEMIK KOGNITIF DALAM PEMBELAJARAN BAHASA CINA - Ariesa Restianti Binawati; Bachtiar S Bachri; Fajar Arianto (Akademika, 2020)
Pronunciations of Chinese that are different from Indonesian pronunciation make beginner learners feel difficult and the need for companions in learning Mandarin. Spelling mistakes make meaning mistakes in Chinese. This requires a language learning model. The Cognitive Academic Language Learning Approach(CALLA) model is a language learning model for the development of foreign language skills according to native speakers. So the CALLA model is used for learning Chinese in order to practice self-directed learning and Mandarin phonetics. This study aims to determine the effectiveness of the CALLA model in Chinese learning in 10th grade. The research method used was a quasi-experimental study in 10th grade with data collection in the form of a response questionnaire to assess learning independence and a performance assessment rubric to assess Mandarin phonetics and then analyzed by using the independent sample t-test. The results of t-test are 0.00<0.05 in phonrtic aspect and 0.014<0.05 in self-directed learning. This suggests that the Cognitive Academic Language Learning Approach Model is effectively used ini the 10th grade Mandarin learning in the phonetics and self-directed learning aspect.